Albert Feuerwerker, editor. Chinese Social and Economic History from the Song to 1900. Report of the American Delegation to a Sino-American Simposium. Ann Arbor, Center for Chinese Studies, The University of Michigan, 1982. VI + 182 pp. (Michigan-Monographs in Chinese Studies No. 45). - Cornejo Bustamante, Romer (Estudios de Asia y África, 1985)
-